Comparison of different Ki67 antibodies in human glioblastomas. Issue 4 (August 1995) - Torp, S H; Johannesen, E; Lindboe, C F
Abstract : Aims —To compare immunostaining between the original Ki67 monoclonal antibody and a new polyclonal Ki67 antibody on frozen and paraffin wax sections of human glioblastomas. Methods —Frozen sections and formalin fixed, paraffin wax embedded sections of the same tumour specimens were included in the study (10 cases). Half of the paraffin wax sections were pretreated in a microwave oven. Standard immunohistochemical techniques were used (avidinbiotin peroxidase complex). Five high power fields were examined using an eye-piece graticule, and 500 to 2000 tumour cells were counted. The labelling index was defined as the percentage of positive tumour cells. Results —The Ki67 monoclonal antibody displayed positive immunostaining in all frozen sections (median labelling index 5·9, range 2·6-11·4) whereas only four paraffin wax sections stained positively and only after pretreatment in a microwave oven. The polyclonal Ki67 antibody elicited positive staining in both frozen sections (median labelling index 13·7, range 6·7-21·5) and in paraffin wax sections (median labelling index 12·0, range 2·2-22·7) but only after pretreatment in a microwave oven. Conclusion —The Ki67 monoclonal antibody is not recommended for use on paraffin wax sections of glioma tissues whereas the new polyclonal Ki67 antibody provides satisfactory immunostaining on both frozen and paraffin wax sections.